Agricultural wastes incorporated to the substrate in the production of scarlet eggplant seedlings - Krause, Marcelo Rodrigo; Vieira Lo Monaco, Paola Alfonsa; Ramalho Haddade, Ismail; Monteiro dos Santo, Géssica; Aparecida Merlo Meneghelli, Lorena; Haddad Souza Vieira, Gustavo (Comunicata Scientiae, 2021)
The use of agricultural residues for seedlings production stands out as an effective sustainable alternative in the production of vegetables. This research aimed to evaluate the effect of increasing concentrations of wastes from the coffee beans drying process (moinha) on substrates composed of coconut fiber, eggshell and commercial substrate in the emergence and quality of scarlet eggplant seedlings. We carried out the experiment with five treatments, as the following: T0 – commercial substrate BioplantÒ; T1- 15% of moinha (MO) + 15% of coconut fiber (FC) + 5% of eggshells (CO) + 65% of commercial substrate (SC); T2 - 30% MO + 15% FC + 5% CO+ 50% SC; T3 - 45% MO + 15% FC + 5% CO + 35% SC; and T4 - 60% MO + 15% FC + 5% CO + 20% SC. We evaluated the emergency speed index, seed emergency, seedling height, stem diameter, shoot, root and total dry mass, Dickson’s Quality Index and the electrical conductivity of the substrates. The addition of moinha concentrations above 15% promotes an increase in electrical conductivity compared to the control and negatively affects the seedlings emergency. Among all treatments, 38% of moinha promotes an increase in the number of leaves, 15% of moinha results in higher plant height, stem diameter, and the highest dry mass accumulation. The alternative substrate containing 15% MO + 15% FC + 5% CO + 65% SC promotes a better development for scarlet eggplants seedlings, being an alternative to the exclusive use of the commercial substrate.